(untitled) (Dissertare, 2022)
In 2020, the highest global temperature and the highest concentration of carbon dioxide (CO2) in our atmosphere for more than 3 million years are recorded. The World Bank (2021) confirms that climate change is advancing and its relationship with human well-being is evident. However, it affirms that countries can still follow a sustainable, strong and inclusive path with a flexible economy. Given the seriousness of this situation, scientific knowledge should contribute to the achievement of sustainable societies, which implies rethinking science and its methods. Faced with these challenges, it is worth asking: Is there a scientific paradigm that responds to the proposals of sustainability? What requirements should a paradigm meet with this approach? This work aims to propose a theoretical and operational definition applicable to the concept of paradigm from a scientific standpoint, within the framework of sustainability. To that purpose, the state of the art is carried out on the descriptions and the structures or dimensions of the paradigms. The work is of a qualitative nature, with documentary design, supported by the use of bibliographic review techniques. The analyzed sources are selected through an intentional non-probabilistic sampling. It is concluded that the definition and paradigmatic structure proposed allows evaluating scientific statements with respect to the status of paradigms, in addition to offering a framework for validating research results, guaranteeing that the methods applied and the solutions proposed contribute to the sustainability of the environment for current and future generations.